Jejak Historis Situs Eksplorasi Minyak Bajubang, Jambi - Azis Faturahman; Aman Aman (Jurnal Sejarah Citra Lekha, 2021)
This article raises a discovery of one of the cities rich in potential oil resources in Indonesia, precisely at Bajubang, Jambi Province. This article is based on research conducted using historical methods including the collection of primary and secondary sources, including archival and literature studies, observations, as well as in-depth interviews. Since the discovery of the first oil in Bajubang Laut in 1916 by the Dutch through their oil company namely, Nederlandsch-Indische Aardolie Maatschappij (NIAM). The oil exploration in Bajubang raised a conflict between the Dutch enterprise and the United States enterprise called Standard Vacuum Petroleum Maatschappij (SVPM). Bajubang exploration site is one of the best and largest in the world that produces the best quality oil up until now. It is pure oil, contains good gas pressure, and low wax content. Bajubang had been ruled by three different eras, including NIAM which was under the Dutch government in 1920-1942, the Japanese colonial period from 1942-1945, and post-independence operated by the Republic of Indonesia Oil Company (PERMIRI) which has been changed to Pertamina. The glory of Bajubang oil exploration site occurred when PERMIRI produced avian turbine products as aircraft fuel. Bajubang exploration site also leaves historical traces such as hospitals, Dutch settlement, Japanese cave, PERMIRI oil refinery, mining equipments, churches, cinemas, schools, oil pipelines, and golf courses.